The Anticancer Activity of Sea Buckthorn [Elaeagnus rhamnoides (L.) A. Nelson] - Olas, Beata; Skalski, Bartosz; Ulanowska, Karolina (Frontiers in Pharmacology, 2018)
Various partss of sea buckthorn (Elaeagnus rhamnoides (L.) A. Nelson), particularly the berries, known also as seaberries or Siberian pineapples, are characterized by a unique composition of bioactive compounds: phenolic compounds, vitamins (especially vitamin C), unsaturated fatty acids, and phytosterols such as beta-sitosterol. These berries, together with the juices, jams, and oils made from them, have a range of beneficial antioxidant, anti-inflammatory, and anticancer effects. This short review discusses whether sea buckthorn may represent a “golden mean” for the treatment of cancers: It has anti-proliferation properties and can induce apoptosis and stimulate the immune system, and sea buckthorn oil counteracts many side effects of chemotherapy by restoring kidney and liver function, increasing appetite, and keeping patients in general good health. Although the anticancer activity of sea buckthorn has been confirmed by many in vitro and animal in vivo studies, the treatment and prophylactic doses for humans are unknown. Therefore, greater attention should be paid to the development of well-controlled and high-quality clinical experiments in this area.